2010
DOI: 10.1021/ic902397w
|View full text |Cite
|
Sign up to set email alerts
|

Prussian Blue Analogues for CO2 and SO2 Capture and Separation Applications

Abstract: Adsorption isotherms of pure gases present in flue gas including CO(2), N(2), SO(2), NO, H(2)S, and water were studied using prussian blues of chemical formula M(3)[Co(CN)(6)](2).nH(2)O (M = Co, Zn) using an HPVA-100 volumetric gas analyzer and other spectroscopic methods. All the samples were characterized, and the microporous nature of the samples was studied using the BET isotherm. These materials adsorbed 8-10 wt % of CO(2) at room temperature and 1 bar of pressure with heats of adsorption ranging from 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 139 publications
(98 citation statements)
references
References 56 publications
5
92
1
Order By: Relevance
“…Recently, Long and others published a series of paper using Prussian blue analogues for hydrogen storage at 77 K [44,45]. In addition to the promising H 2 storage materials, the cyano-bridged frameworks may be useful for CO 2 storage and separation applications [46,47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Long and others published a series of paper using Prussian blue analogues for hydrogen storage at 77 K [44,45]. In addition to the promising H 2 storage materials, the cyano-bridged frameworks may be useful for CO 2 storage and separation applications [46,47].…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to the fact that the unsaturated metal centers of the framework interact with O 2 more strongly than with N 2 [49]. Other cyano-bridged coordination solids containing coordinatively unsaturated metal centers have been shown to interact with H 2 at high loading [44,45]. The maximum O 2 uptake is 3.39 wt.%, which corresponds to approximately 0.67 O 2 molecules per formula unit of 2.…”
Section: Resultsmentioning
confidence: 99%
“…1 was used to estimate the ratio of the sensitivity factors for the characteristic peaks for CO 2 (ad) at 2339 cm −1 and SO 2 (ad) at 1146 cm −1 that were selected as the molecular markers in this study. Sorption data from Thallapally et al [5] indicate that approximately 6.25 times as much SO 2 (per mole) is adsorbed than CO 2 on CoCo, in separate experiments at 298 K when each gas is at ∼10 kPa. Consequently,…”
Section: Infrared Peak Assignments and Intensitiesmentioning
confidence: 94%
“…First, the gas is a known component of CO 2 waste streams at concentrations on the order of 1% (taken as mole percent in this study). It is also being investigated in volumetric sorption studies on CoCo in our laboratory [5], is strongly infrared active in the gas phase, and the occurrence of infrared peaks due to adsorbed SO 2 seemed likely since recent transmission studies have reported them for other adsorbents [6,7]. Finally, while the two gases are not isostructural, their molecular diameters are comparable suggesting they might be similarly accommodated within the pores of CoCo.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the adsorbed SO 2 can be readily released, and the NOTT-300 regenerated at ambient temperatures without the need for heating, indicating an easy-on/easy-off capture system. Thallapally et al 65 studied SO 2 and H 2 S adsorption in some Prussian blue analogs, M 3 [Co(CN) 6 ] 2 ⋅ nH 2 O (M = Co, Zn). They showed that the Co 3 [Co(CN) 6 ] 2 can adsorb a significant amount of SO 2 and H 2 S, with capacities of 10 and 4.5 wt% at 100 kPa, respectively.…”
Section: Inorganic Toxic Gas Removalmentioning
confidence: 99%